Healthcare resource utilization following unilateral versus bilateral radiation therapy for oropharyngeal carcinoma. (March 2021) - Hosni, Ali; Huang, Shao Hui; Xu, Wei; Su, Jie; Watson, Erin; Glogauer, Michael; Bayley, Andrew; Bratman, Scott V.; Cho, John; Giuliani, Meredith; Hope, Andrew; Kim, John; et al.
Highlights: Bilateral RT increased short-term healthcare service utilization. Bilateral RT increased long-term healthcare service utilization. Future research is required for appropriate selection of patients to unilateral RT. Abstract: Purpose: To describe differences in healthcare resource utilization between patients treated with bilateral vs. unilateral neck radiation therapy (RT) for lateralized oropharyngeal cancer. Methods: A propensity score matching strategy was used to identify two otherwise clinically similar cohorts of tonsillar cancer patients treated with either bilateral or unilateral neck RT. Cohorts were matched based on similar propensity scores for age, sex, ECOG performance status, pack-year smoking history, cT-category, cN-category, HPV-status, and use of concurrent chemotherapy. Short term (from start of RT to 3 months following end of RT) resource utilization included: 1) outpatient supportive care visits, 2) hospital admission, and 3) interventions (feeding tube insertion and outpatient intravenous hydration). Long-term resource utilization included feeding tube dependency at 1-year. Results: Among 559 patients with tonsillar cancer treated between 2004–2017, propensity score matching identified a unilateral neck RT cohort ( n = 81) and bilateral neck RT cohort ( n = 81) with similar clinical and treatment characteristics. Bilateral neck RT was associated with a higher likelihood of hospitalization (33% vs 12%, p < 0.01), outpatient IV hydration (33% vs 17%, p = 0.03), and feeding tube insertion (33% vs 10%, p < 0.001); a greater number of total days of hospitalization (110 vs 47 days, p < 0.01) and outpatient IV hydration (135 vs 72 days, p = 0.02); and higher total number of supportive clinic visits (1226 vs 1053 days, p = 0.04). In the long-term, bilateral RT was associated with higher rate of feeding tube dependency at 1-year (7% vs 0%, p < 0.001). Conclusion: Bilateral RT for tonsillar cancer resulted in significant increase in health resource utilization.